Chat Gpt : Improving Biology Learning Outcomes Problem-Based Learning Assisted Artificial Intelligence - Rahaf Faldi, Muhammad Risyad; Prafitasari, Aulya Nanda; Soelfiah, Arlien (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
Learning outcomes are an assessment of success in education, where success is achieved when learning objectives are met. To measure this achievement, learning outcome tests are used by providing numerical assessments. This research study aims to identify the improvement of students' cognitive learning outcomes through the implementation of the Problem-Based Learning (PBL) model assisted by Artificial Intelligence (AI): ChatGpt. Cognitive learning outcomes hold significant value as they are used as indicators to evaluate the achievement of learning objectives and provide benefits for students in developing their thinking abilities to tackle various problems. The research adopts a quantitative descriptive approach, with the research subjects being students of X - 5 class at SMAN X Purwosari. The Classroom Action Research (CAR) was conducted during the period of March to May 2023, consisting of two cycles. The CAR stages include planning, implementation, observation, and reflection. The research results demonstrate a significant improvement in students' cognitive learning outcomes, with an increase of 25% in cycle 1 and 77% in cycle 2.ABSTRAK: Hasil pembelajaran adalah penilaian keberhasilan dalam pendidikan, di mana keberhasilan dicapai ketika tujuan pembelajaran terpenuhi. Untuk mengukur pencapaian ini, ujian hasil pembelajaran digunakan dengan memberikan penilaian numerik. Penelitian ini bertujuan untuk mengidentifikasi peningkatan hasil belajar kognitif siswa melalui implementasi model Pembelajaran Berbasis Masalah (PBM) yang dibantu oleh Kecerdasan Buatan (AI): ChatGpt. Hasil belajar kognitif memiliki nilai yang signifikan karena digunakan sebagai indikator untuk mengevaluasi pencapaian tujuan pembelajaran dan memberikan manfaat bagi siswa dalam mengembangkan kemampuan berpikir mereka untuk mengatasi berbagai masalah. Penelitian ini mengadopsi pendekatan deskriptif kuantitatif, dengan subjek penelitian adalah siswa kelas X - 5 di SMAN X Purwosari. Penelitian Tindakan Kelas (PTK) dilakukan selama periode Maret hingga Mei 2023, yang terdiri dari dua siklus. Tahapan PTK meliputi perencanaan, implementasi, observasi, dan refleksi. Hasil penelitian menunjukkan peningkatan signifikan dalam hasil belajar kognitif siswa, dengan peningkatan sebesar 25% pada siklus 1 dan 77% pada siklus 2.